RISK-MANAGEMENT IN UNIVERSITY EDUCATIONAL QUALITY MANAGEMENT - Evgeniya A. Opfer (Высшее образование в России)
The article focuses on the features of University risk-management. The article shows the groups of the risks in higher education, which are based on the risk-management theory and international ISO%standards of risk-management and quality management. The author grounds the following risks for Universities: personnel risks, contingent risks, image-risks, procedural risks, management risks, innovative risks, industrial risks, financial risks, social risks, governmental risks and risks of organizations. They can be divided into three groups: inside, outside and edge risks. The author also describes three levels of managerial decision at University: the top management level, the level of a chair or a department, the level of a teacher or employee. The groups of risks were explained on every managerial level. The author comes to the conclusion that collective risk management is the most effective way to manage the risks and to improve higher education quality.